Comparing seeds germination of some local plant species on two hydroseeding mulches for post mining revegetation - M F Anshari; A A R Fernandes; E Arisoesilaningsih (Journal of Degraded and Mining Lands Management, 2018)
The aims of this study were to determine seed germination rate of some local plant species in two hydroseeding mulches containing different tackifier concentration, as well as to determine the optimal hydroseeding mulch media composition for germinating seeds. This study used seeds of 13 local plant species: two species of Cyperaceae (Cyperus brevifolius, C. javanicus), five species of Leguminosae (Cajanus cajan, Crotalaria pallida, Sesbania grandiflora, S. sesban, Tephrosia purpurea), and six species of Poaceae (Eleusine indica, Paspalum conjugatum, Sorghum timorense, S. bicolor, Sporobolus indicus, Themeda arundinaceae). Two hydroseeding mulch media with different tackifier composition were mixed with seeds of each species and then sowed in pots. Each treatment was repeated three times. Moistened cotton wool was used as control and comparative media for observing seed viability. Seed germination in mulch media was observed during 13 days. The results showed that only 8 of 13 species could be germinated: S. indicus, S. timorense, T. arundinaceae, C. cajan, C. pallida, S. grandiflora, S. sesban, and T. purpurea. The highest germination rate was shown by S. sesban (67%) in M2 medium and the lowest one was shown by T. arundinaceae (2%) in both media. The fastest germination time was recorded for C. pallida and S. sesban seeds that germinated in 2 days after sowing (DAS) in both media, while S. timorense and T. arundinaceae seeds showed the lowest ones in 11 DAS. The fluid M1 medium was optimal for seeds germination of S. sesban (50%) and S. grandiflora (35%), while the thicker M2 medium was optimal for seeds germination of S. sesban (67%) and S. timorense (50%) in 13 DAS. The maximum germination rate was generally reached in 11 DAS.